2009
DOI: 10.1111/j.1742-4658.2009.06866.x
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid discrimination by arginyl‐tRNA synthetases as revealed by an examination of natural specificity variants

Abstract: l‐Canavanine occurs as a toxic non‐protein amino acid in more than 1500 leguminous plants. One mechanism of its toxicity is its incorporation into proteins, replacing l‐arginine and giving rise to functionally aberrant polypeptides. A comparison between the recombinant arginyl‐tRNA synthetases from a canavanine producer (jack bean) and from a related non‐producer (soybean) provided an opportunity to study the mechanism that has evolved to discriminate successfully between the proteinogenic amino acid and its n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…A similar analysis confirms previous observations [26] reporting that discrimination by the plant enzyme is also sensitive to structural changes in the tRNA (Fig. 11).…”
Section: Soybean Arginyl‐trna Synthetasesupporting
confidence: 92%
See 4 more Smart Citations
“…A similar analysis confirms previous observations [26] reporting that discrimination by the plant enzyme is also sensitive to structural changes in the tRNA (Fig. 11).…”
Section: Soybean Arginyl‐trna Synthetasesupporting
confidence: 92%
“…This is toxic to nonproducers, such as soybean, as a result of its incorporation into proteins via misrecognition by the arginyl‐tRNA synthetase [33]. We have previously shown that the structure of the tRNA can influence the discriminating ability of soybean arginyl‐tRNA synthetase [26]. In an approach aiming to determine the role, if any, of tRNA identity elements in amino acid discrimination, we have investigated the structural features that are responsible for tRNA recognition by the arginyl‐tRNA synthetase from the two related higher plants and compared these with previously documented elements in E. coli .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations